Neuromodulation of the Cardiac Autonomic Nervous System for Arrhythmia Treatment - Benjamin Wong; Yuki Kuwabara; Siamak Salavatian (Biomedicines)
This review explores current and emerging neuromodulation techniques targeting the cardiac autonomic nervous system for the treatment and prevention of atrial and ventricular arrhythmias. Arrhythmias remain a significant cause of morbidity and mortality, with the autonomic nervous system playing a crucial role in arrhythmogenesis. Interventions span surgical, pharmacological, and bioelectronic methods. We discuss the range of neuromodulation methods targeting the stellate ganglion, the spinal region, the parasympathetic system, and other promising methods. These include stellate ganglion block, stellate ganglion ablation, cardiac sympathetic denervation, subcutaneous electrical stimulation, thoracic epidural anesthesia, spinal cord stimulation, dorsal root ganglion stimulation, vagus nerve stimulation, baroreflex activation therapy, carotid body ablation, renal denervation, ganglionated plexi ablation, acupuncture, and transcutaneous magnetic stimulation. Both preclinical and clinical studies are presented as evidence for arrhythmia management.